Microbiome and Functional Analysis of a Traditional Food Process: Isolation of a Novel Species (Vibrio hibernica) With Industrial Potential - Woods, David F.; Kozak, Iwona M.; O’Gara, Fergal (Frontiers in Microbiology, 2020)
Traditional food preservation processes are vital for the food industry. They not only preserve a high-quality protein and nutrient source but can also provide important value-added organoleptic properties. The Wiltshire process is a traditional food curing method applied to meat, and special recognition is given to the maintenance of a live rich microflora within the curing brine. We have previously analyzed a curing brine from this traditional meat process and characterized a unique microbial core signature. The characteristic microbial community is actively maintained and includes the genera, Marinilactibacillus, Carnobacterium, Leuconostoc, and Vibrio. The bacteria present are vital for Wiltshire curing compliance. However, the exact function of this microflora is largely unknown. A microbiome profiling of three curing brines was conducted and investigated for functional traits by the robust bioinformatic tool, Tax4Fun. The key objective was to uncover putative metabolic functions associated with the live brine and to identify changes over time. The functional bioinformatic analysis revealed metabolic enrichments over time, with many of the pathways identified as being involved in organoleptic development. All of the core bacteria present in the brine are Lactic Acid Bacteria (LAB), with the exception of the Vibrio genus. LAB are known for their positive contribution to food processing, however little work has been conducted on the use of Vibrio species for beneficial processes. The Vibrio genome was sequenced by Illumina MiSeq technologies and annotated in RAST. A phylogenetic reconstruction was completed using both the 16S rRNA gene and housekeeping genes, gapA, ftsZ, mreB, topA, gyrB, pyrH, recA and rpoA. The isolated Vibrio species was defined as a unique novel species, named Vibrio hibernica. Metabolic profiling revealed that the bacterium has a unique substrate scope in comparison to other closely related Vibrio species tested. The possible function and industrial potential of the strain was investigated using carbohydrate metabolizing profiling under food processing relevant conditions. Vibrio hibernica is capable of metabolizing a unique carbohydrate profile at low temperatures. This characteristic provides new application options for use in the industrial food sector, as well as highlighting the key role of this bacterium in the Wiltshire curing process.